Pan-conserved segment tags identify ultra-conserved sequences across assemblies in the human pangenome - Lee, HoJoon; Greer, Stephanie U.; Pavlichin, Dmitri S.; Zhou, Bo; Urban, Alexander E.; Weissman, Tsachy; Ji, Hanlee P.; Liao, Wen-Wei; Asri, Mobin; Ebler, Jana; Doerr, Daniel; Haukness, Marina; et al. (Cell reports methods, 2023)
The human pangenome, a new reference sequence, addresses many limitations of the current GRCh38 reference. The first release is based on 94 high-quality haploid assemblies from individuals with diverse backgrounds. We employed a k-mer indexing strategy for comparative analysis across multiple assemblies, including the pangenome reference, GRCh38, and CHM13, a telomere-to-telomere reference assembly. Our k-mer indexing approach enabled us to identify a valuable collection of universally conserved sequences across all assemblies, referred to as "pan-conserved segment tags" (PSTs). By examining intervals between these segments, we discerned highly conserved genomic segments and those with structurally related polymorphisms. We found 60,764 polymorphic intervals with unique geo-ethnic features in the pangenome reference. In this study, we utilized ultra-conserved sequences (PSTs) to forge a link between human pangenome assemblies and reference genomes. This methodology enables the examination of any sequence of interest within the pangenome, using the reference genome as a comparative framework.